Virtual Communication Embedded Bedside ICU Rounds: A Hybrid Rounds Practice Adapted to the Coronavirus Pandemic. Issue 8 (August 2021) - Bavare, Aarti C.; Goldman, Jordana R.; Musick, Matthew A.; Sembera, Kerry A.; Sardual, Alex A.; Lam, Anne K.; Tume, Sebastian C.; Thammasitboon, Satid X.; Williams, Eric A.
Abstract : OBJECTIVES: Coronavirus disease 2019 containment strategies created challenges with patient-centered ICU rounds. We examined how hybrid rounds with virtual communication added to in-person rounds could facilitate social distancing while maintaining patient-centered care. DESIGN: Continuous quality improvement. SETTING: Quaternary care referral pediatric hospital. PATIENTS: Daytime rounds conducted on PICU patients. INTERVENTIONS: Following a needs assessment survey and pilot trials, multiple technological solutions were implemented in a series of plan-do-study-act cycles. Hybrid rounds model was deployed where a videoconference platform was used to establish communication between the bedside personnel (nurse, patient/family, and partial ICU team) with remotely located remaining ICU team, ancillary, and consultant providers. Floor labels marking 6-feet distance were placed for rounders. MEASUREMENTS AND MAIN RESULTS: Outcome metrics included compliance with social distancing, mixed methods analysis of surveys, direct interviews of providers and families, and reports of safety concerns. The clinicians adopted hybrid rounds readily. Compliance with social distancing and use of floor labels needed reminders. One-hundred fourteen providers completed the feedback survey. Twenty-five providers and 11 families were interviewed. Feedback about hybrid rounds included inability to teach effectively, suboptimal audio-video quality, loss of situational awareness of patient/unit acuity, alarm interference, and inability to socially distance during other ICU interactions. Benefits noted were improved ancillary input, fewer interruptions, improved efficiency, opportunity to integrate with data platforms, and engage remote consultants and families. Nurses and families appreciated the efforts to ensure safety but wanted the ICU attending/fellow supervising the team to participate at bedside, during rounds. Clinicians appreciated the multidisciplinary input but felt that teaching was difficult. CONCLUSIONS: Hybrid rounds employed during pandemic facilitated social distancing while retaining patient-centered multidisciplinary ICU rounds but compromised teaching during rounds. A change to ingrained rounding habits needs team commitment and ongoing optimization. The hybrid rounds model has potential for generalizability to other settings. Abstract : Supplemental Digital Content is available in the text.